P53 Inhibition Protects against Neuronal Ischemia/Reperfusion Injury by the p53/PRAS40/mTOR Pathway. (3rd December 2021) - Zhao, Jianlan; Dong, Yinhui; Chen, Xingyu; Xiao, Xiao; Tan, Bo; Chen, Gong; Hu, Jin; Qi, Dashi; Li, Xiaomu; Xie, Rong
Abstract : The underlying mechanisms of cerebral ischemia/reperfusion (I/R) injury are unclear. Within this study, we aimed to explore whether p53 inhibition exerts protective effects via the p53/PRAS40/mTOR pathway after stroke and its potential mechanism. Both an in vitro oxygen-glucose deprivation (OGD) model with a primary neuronal culture and in vivo stroke models (dMCAO or MCAO) were used. We found that the infarction size, neuronal apoptosis, and autophagy were less severe in p53 KO mice and p53 KO neurons after cerebral I/R or OGD/R injury. By activating the mTOR pathway, p53 knockdown alleviated cerebral I/R injury both in vitro and in vivo. When PRAS40 was knocked out, the regulatory effects of p53 overexpression or knockdown against stroke disappeared. PRAS40 knockdown could inhibit the activities of the mTOR pathway; moreover, neuronal autophagy and apoptosis were exacerbated by PRAS40 knockdown. To sum up, in this study, we showed p53 inhibition protects against neuronal I/R injury after stroke via the p53/PRAS40/mTOR pathway, which is a novel and pivotal cerebral ischemic injury signaling pathway. The induction of neuronal autophagy and apoptosis by the p53/PRAS40/mTOR pathway may be the potential mechanism of this protective effect.